Reinventing liberal Christianity - Hobson, Theo. (Grand Rapids, Mich. : William B. Eerdmans, 2013)
In past years liberal Christianity challenged centuries of authoritarian tradition and had great political influence. Today it is widely dismissed as a watering-down of the faith, and more conservative forms of Christianity are increasingly dominant. Can the liberal Christian tradition recover its influence? Hobson argues that a simple revival is not possible, because liberal Christianity consists of two traditions. He aims to transform liberal Christianity through the rediscovery of faith and ritual.
Roots -- The frail vision -- The sacramental deficiency -- The allure of reason -- American disestablishment -- Golden age? -- Beyond progress -- The reaction -- The collapse -- Postliberals -- Conclusion : cultic-liberal Christianity.
Includes bibliographical references and index.
Print version record.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Liberalism (Religion); Liberalism (Religion); RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Electronic books